Association Between a Physical Activity Vital Sign and Cardiometabolic Disease in High-Risk Patients. Issue 4 (July 2020) - Nelson, Vicki R.; Masocol, Robert V.; Ewing, Joseph A.; Johnston, Sheri; Hale, Allyson; Wiederman, Michael; Asif, Irfan M.
Abstract : Objective: To determine the association between the physical activity vital sign (PAVS) and markers of cardiometabolic disease. Design: Patients were assessed through the PAVS, a validated tool self-reporting the frequency and duration of physical activity. Patients were categorized into 3 groups: inactive (0 minutes per week), underactive (1-149 minutes per week), and active (>150 minutes per week). Associations were tested between the PAVS and the cardiometabolic disease biomarkers of body mass index, hemoglobin A1c (A1c), blood pressure, and low-density lipoprotein (LDL) using one-way analyses of variance. Setting: High-risk family medicine residency clinic. Participants: Two thousand three hundred twenty-one adult patients (age ≥ 18 years). Results: Participants reported a mean of 97.87 (SD = 149.35) minutes per week of exercise. Overall, 50.1% reported physical inactivity, 25.7% were underactive, and 24.3% were active. Younger individuals ( P < 0.001) and men ( P < 0.05) reported more physical activity than older individuals and women. Patients who reported being active were significantly less likely to be overweight ( P < 0.05), obese ( P < 0.05), or hypertensive ( P < 0.05), but there was no association with A1c or LDL levels. Conclusions: This is the first investigation to examine the PAVS in a high-risk population. In these patients, reported levels of physical inactivity are 150% higher than other clinical settings, and the PAVS is only associated with improvements in 2 of 4 major cardiometabolic risk factors. For this group, self-reported levels of physical activity may need to be higher for cardiovascular benefits to be realized in all 4 cardiometabolic domains. The PAVS offers health professionals an opportunity to encourage lifestyle-based interventions to reduce cardiovascular risk, but refinements may be necessary to address this population.